THE EFFECT OF USING THINK ALOUD TECHNIQUE ON THE STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Jamik alfiansyah Alfiansyah (Graduate Program, University of Islam Malang, 2021)
The purpose of this study is to investigate the effectiveness of using “Think Aloud Technique” on the eleventh-grade students reading comprehension achievement at one of “Vocational School in East Java Indonesia”. Quasi-experimental research is the design of this study that employs “XI A1” as the experimental group and “XI A2” as the control group. The experimental group got treatment by “Think Aloud” technique while the control group had no treatment but taught by using group discussion technique. The researcher conducted this study in four meetings, three meetings for giving treatment in the class, and a meeting for conducting the post-test. The data was collected by using multiple choice reading comprehension tests. The data obtained were analyzed by using the independent t-test formula. Result of data analysis showed that there is a significant effect of using the think aloud technique on the eleventh-grade students’ reading comprehension achievement in Vocational School in East Java (p=.034).